System models and model classification in tribological system development. Issue 6 (2nd November 2020) - Faustmann, Clemens; Bajzek, Matthias; Hick, Hannes; Edtmayer, Josef; Walch, Simon
Abstract: Current requirements for the reduction of CO2 emissions, as well as for the improvement of durability and reliability of sociotechnical systems such as passenger cars, lead to an increase in development effort in order to increase efficiency and system lifetime. Tribological systems play an essential role in the development of sociotechnical systems, but have proved to be particularly complex. The development of tribological systems, as part of the overall system under development, is an interdisciplinary effort. Involvement of solid mechanics, fluid mechanics, rheology, and many more scientific disciplines is essential to cope with the high number of nonlinear relationships, which often cause unpredictable system behavior. This paper contributes to the scientific field of tribology by introducing concepts of model‐based systems engineering for the specific case of elastohydrodynamic lubrication states. The elastohydrodynamic lubrication state of tribological system has been chosen as example to show how system models can be used to better describe the behavior of a system by connecting several specific models. In order to gain an overview of the models used in tribological system development, a system cube was used to structure the models. The system cube enabled gaps and overlapping model zones to be identified. Finally, the role of system models in development and the benefit of using system models to solve problems that cannot be solved by a single technical discipline but only in an interdisciplinary effort are discussed. An approach to connect models and methods to describe a system in an elastohydrodynamic lubrication state is presented.